Pengembangan Sistem Monitoring Pengelolaan Anggaran Proyek Berbasis Web Menggunakan CodeIgniter pada PT ABCD - Nurul Rahmawati; Sugih Sutrisno Putra (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The project budget management monitoring system at PT ABCD is still done manually using spreadsheets, which are prone to errors and delays in information. This research aims to develop a web-based monitoring system using the CodeIgniter framework to enable real-time budget management that can be accessed anytime and anywhere. The system development method used is the System Development Life Cycle (SDLC) waterfall model, with Black Box testing to ensure all functionality is running properly. The application is designed using the PHP programming language, CodeIgniter framework, and MySQL database. The developed system includes dashboard modules, monitoring, submission and use of advances, recapitulation, reports, and master data containing COA, account, and project data. The implementation results show that the system is able to improve process efficiency, reduce recording errors, and strengthen budget monitoring and reporting functions in an accurate and structured manner. All features have been tested and run according to user needs. Thus, this system is expected to increase transparency, accountability, and internal control in project budget management in the company.